Genetic interrelationship between insulin-dependent diabetes mellitus, the autoimmune thyroid diseases, and rheumatoid arthritis. - Torfs, C P (1986)
To investigate the possible coinheritance of autoimmune diseases that are associated with the same HLA antigen, we studied 70 families in which at least two siblings had either type I diabetes mellitus (IDDM), autoimmune thyroid disease (ATD), rheumatoid arthritis (RA), or a combination of these diseases. HLA-A, B, and C typing was performed on all affected sibs in one generation or more. First, we estimated by sib-pair analysis the disease allele frequency (pD) and the mode of inheritance for each disease. According to the method of ascertainment entered into the analysis, the pD for ATD ranged from .120 to .180, for an additive (dominant) mode of inheritance. For RA, the pD ranged from .254 to .341, also for additive inheritance, although recessive inheritance could not be excluded. For IDDM, the pD ranged from .336 to .337 for recessive inheritance; additive inheritance was rejected. Second, we examined the distribution of shared parental haplotypes in pairs of siblings that were discordant for their autoimmune diseases. The results suggested that the same haplotype may predispose to both IDDM and ATD, or IDDM and RA, but not to both RA and ATD. Analysis of pedigrees supported this hypothesis. In 16 families typed for HLA-DR also, the haplotype predisposing to both IDDM and ATD was assigned from pedigree information to DR3 (44%), DR4 (39%), or DR5, DR6, or DR7 (5.5% each). In some families, these haplotypes segregated over several generations with ATD only (either clinical or subclinical), suggesting that in such families, ATD was a marker for a susceptibility to IDDM. In several families, an IDDM haplotype segregated with RA but not with ATD. This suggests that ATD- and RA-associated susceptibilities to IDDM may be biologically different and thus independently increase the risk of IDDM.